Catalyzing industrial decarbonization: the promissory legitimacy of Fossil Free Sweden. Issue 1 (12th July 2022) - Brodén Gyberg, Veronica; Lövbrand, Eva
Abstract: In 2017, the Swedish parliament adopted a new climate policy framework that lays the foundations for an ambitious decarbonization of all sectors in Swedish society. To live up to the Paris Agreement's temperature targets, the parliament decided that Sweden should arrive at net zero emissions of greenhouse gases by year 2045 and thereafter aim for net negative emissions. This progressive climate policy agenda is embedded in a strong collaborative discourse. To begin the transition to a fossil-free society, the Swedish government has invited a wide array of actors to join forces in the formulation and implementation of low carbon initiatives. In this paper we examine the fossil-free society as a powerful socio-technical imaginary that underpins this collaborative effort. We trace the promise attached to this future dreamscape and how it is mobilized by the government initiative Fossil-Free Sweden (FFS) to gain support for industrial decarbonization in the present. Our study draws upon roadmaps produced by FFS together with the Swedish steel, cement, and petroleum industry, as well as semi-structured interviews with selected industry actors. We find that the FFS roadmaps work as powerful "techniques of futuring" that invite industry actors to anticipate the risks and opportunities attached to the fossil-free society and at the same time contribute to shaping that society. While effectively involving incumbent actors in the political project of decarbonization, our study suggests that the roadmaps consolidate around an imagined future that is a techno-optimistic extension of the fossil-intensive present.